CHRONIC INFLAMMATORY SCORE IN PATIENTS WITH DACRYOCYSTORHINOSTOMY AND CORRELATION WITH SURGICAL OUTCOME - Shahid, Erum; Shahid, Ruqaiya; Fasih, Uzma; Jafri, Asad Raza (Journal of Ayub Medical College Abbottabad, 2024)
Background: Dacryocystorhinostomy (DCR) is an ophthalmic surgical procedure for relieving obstruction from chronically inflamed nasolacrimal duct (chronic dacryocystitis). This study was performed to observe the surgical outcome of DCR in patients with chronic dacryocystitis; to grade the inflammation in lacrimal sac biopsies, using the chronic inflammatory score (CIS); and to correlate the CIS with the surgical outcome. Methods: Twenty-five patients with chronic dacryocystitis underwent DCR with lacrimal sac biopsies. The biopsies were examined microscopically, and a CIS score was assigned and graded into mild, moderate and severe. The patients were followed up. The success of DCR was evaluated at 6 months post-surgery, by syringing of the lacrimal tract. Results: The mean age of the patients was 37.76 years±12.32 SD. The mean duration of watering of the eye was 2.9 years±3.18 years. The right eye was involved in 60% and 80% of the patients were females. Severe inflammation was reported in 72%, moderate angiogenesis in 76% and moderate fibrosis in 72%, squamous metaplasia in 40%, and a reduced number of goblet cells in 72% of the biopsies. CIS was severe in 72% of the patients. At 6 months follow-up, 96% of the patients had a successful DCR. Conclusion: Although the chronic inflammatory score was severe, the DCR was successful in most of the patients, suggesting that the success of the surgical procedure is not related to the degree of inflammation. Large-scale studies are recommended for confirmation of our findings